2007
DOI: 10.1002/chem.200601482
|View full text |Cite
|
Sign up to set email alerts
|

Substrate‐Controlled and Site‐Selective [3+2] Cycloadditions of NHeterocyclic Carbene Derived Ambident Dipoles

Abstract: 2-aryl thiocarbamoyl benzimidazolium and imidazolinium inner salts derived from benzimidazole and imidazoline carbenes are unique ambident C-C-S and C-C-N 1,3-dipolar systems, which undergo highly efficient and site-selective cycloaddition reactions with dimethyl acetylenedicarboxylate or dibenzoylacetylene to furnish spiro(imidazole-2,3'-thiophene) derivatives in excellent yields. When treated with ethyl propiolate, methyl acrylate or acrylonitrile, spiro(imidazole-2,3'-pyrrole) derivatives were formed in goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…6 2-Aryl thiocarbamoyl benzimidazolium salts derived from benzimidazole and imidazoline carbenes undergo cycloaddition reactions with DBD to furnish spiro(imidazole-2,3'-thiophenes). 7 Protonation of the highly reactive 1 : 1 intermediates produced in the reaction between alkyl isocyanides and DBD leads to vinylnitrilium cations, which undergo carbon-centred Michael type addition with the conjugate base of the NH-acid to produce highly functionalised aminofuran derivatives. 8 It is reported that amidrazones condense only with dicarbonyl compounds to yield 1,2,4-triazines.…”
mentioning
confidence: 99%
“…6 2-Aryl thiocarbamoyl benzimidazolium salts derived from benzimidazole and imidazoline carbenes undergo cycloaddition reactions with DBD to furnish spiro(imidazole-2,3'-thiophenes). 7 Protonation of the highly reactive 1 : 1 intermediates produced in the reaction between alkyl isocyanides and DBD leads to vinylnitrilium cations, which undergo carbon-centred Michael type addition with the conjugate base of the NH-acid to produce highly functionalised aminofuran derivatives. 8 It is reported that amidrazones condense only with dicarbonyl compounds to yield 1,2,4-triazines.…”
mentioning
confidence: 99%
“…Subsequent efforts were directed toward analyzing the reaction of 1 with isothiocyanates, substrates that typically afford imidothioates when exposed to NHCs . Stirring a C 6 H 6 solution of 1 with an equimolar amount of 4‐nitrophenyl isothiocyanate at room temperature for 1 h ([ 1 ] 0 = 0.13 M) resulted in the formation of dihydropyrimidinium imidothioate 3 (Scheme ), as evidenced by the FT‐IR carbonyl stretching frequencies observed at 1769 and 1740 cm −1 and the 1:1 DAC:isothiocyanate stoichiometry gleaned from 1 H NMR spectroscopic analysis of the crude reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…These reactions are generally rapid, proceed with complete atom economy, and give high yields of products that are attractive for the synthesis of heteroatom rich compounds . Moreover, such carbene–heteroallene coupling reactions have been used in applications that range from small molecule activation and catalysis to the synthesis of novel polymers and heterocycles …”
Section: Introductionmentioning
confidence: 99%
“…Formation of NHCs can proceed via the corresponding metal-carbene complex [49], from the elimination of a haloform (CHX 3 ) [50], or from deprotonation of an imidazolium species [51, 52]. Elimination of carbamates, analogous to the urea elimination observed by Ulrich et al has been described as well in the synthesis of NHCs [53].…”
Section: Synthesis Of Triazaspirocyclesmentioning
confidence: 99%